Penguasaan Dan Penggunaan Tanah Oleh Warga Negara Asing Berdasarkan Perjanjian Sewa Menyewa Di Pulau Kepa Desa Alor Kecil Kecamatan Alor Barat Laut Kabupaten Alor - Tanhi, Semi Yusup; Nubatonis, Orpa J (Artemis Law Journal, 2025)
This study is an empirical research that aims to find out and analyze foreign countries based on lease agreements on Kepa Island, Alor Kecil Village, Alor Barat District, Alor Regency. This research was conducted on Kepa Island. The types of data used are primary data and secondary data. The data collection techniques used are through interviews and literature studies. The population in this study is the head of the land office, village head, foreign citizens, and local communities who make lease agreements with foreign citizens. The sample used in this study is a saturated sample technique with a total of 7 respondents. This study shows that the ownership and use of land by foreign nationals through lease agreements requires special attention in terms of regulations and their implementation to ensure that existing regulations can be optimized to support responsible and sustainable investment in the area so that national interests and community welfare are maintained.